Sentinel lymph node biopsy in microinvasive ductal carcinoma in situ. Issue 4 (21st February 2019) - Magnoni, F.; Massari, G.; Santomauro, G.; Bagnardi, V.; Pagan, E.; Peruzzotti, G.; Galimberti, V.; Veronesi, P.; Sacchini, V. S.
Abstract : Background: Microinvasive breast cancer is an uncommon pathological entity. Owing to the rarity of this condition, its surgical axillary management and overall prognosis remain controversial. Methods: A database was analysed to identify patients with microinvasive ductal carcinoma in situ (DCIS) who had surgery for invasive breast cancer at the European Institute of Oncology, Milan, between 1998 and 2010. Women who had undergone axillary staging by sentinel lymph node biopsy were included in the study. Results: Of 257 women with microinvasive breast cancer who underwent sentinel lymph node biopsy (SLNB), 226 (87·9 per cent) had negative sentinel lymph nodes (SLNs) and 31 had metastatic SLNs. Twelve patients had isolated tumour cells (ITCs), 14 had micrometastases and five had macrometastases in sentinel nodes. Axillary lymph node dissection was performed in 16 of the 31 patients with positive SLNs. After a median follow‐up of 11 years, only one regional first event was observed in the 15 patients with positive SLNs who did not undergo axillary lymph node dissection. There were no regional first events in the 16 patients with positive SLNs who had axillary dissection. Conclusion: Good disease‐free and overall survival were found in women with positive SLNs and microinvasive DCIS. This study is in line with studies showing that SLNB in microinvasive DCIS may not be useful, and supports the evidence that less surgery can provide the same level of overall survival with better quality of life. Abstract : No added value